2016
DOI: 10.1371/journal.pone.0152686
|View full text |Cite
|
Sign up to set email alerts
|

GUIdock: Using Docker Containers with a Common Graphics User Interface to Address the Reproducibility of Research

Abstract: Reproducibility is vital in science. For complex computational methods, it is often necessary, not just to recreate the code, but also the software and hardware environment to reproduce results. Virtual machines, and container software such as Docker, make it possible to reproduce the exact environment regardless of the underlying hardware and operating system. However, workflows that use Graphical User Interfaces (GUIs) remain difficult to replicate on different host systems as there is no high level graphica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 29 publications
0
49
0
1
Order By: Relevance
“…There are also initiatives for standardizing containers in the life sciences such as BioContainers [11] . Containers have seen an increasing uptake in the life sciences, both for delivering software tools and for facilitating data analysis in various ways [12][13][14][15][16] .…”
Section: Containersmentioning
confidence: 99%
“…There are also initiatives for standardizing containers in the life sciences such as BioContainers [11] . Containers have seen an increasing uptake in the life sciences, both for delivering software tools and for facilitating data analysis in various ways [12][13][14][15][16] .…”
Section: Containersmentioning
confidence: 99%
“…Many traditional software and tools are available on Docker Hub and it is widely used with around five billion software containers downloaded from the repository up to August, 2016 (https://blog.docker.com/2016/08/docker-hub-hits-5-billion-pulls/). In Bioinformatics, there are already tools that are available as Docker software containers and explore features such as reproducibility (Hung et al, 2016; Belmann et al, 2015) or applications areas such as transcriptomics (Zichen et al, 2016). Di Tommaso et al (2015) showed that containers have a negligible impact on the performance of bioinformatics applications.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described and implemented GUIdock-X11 [3], an X11-based methodology for portably supporting GUI applications in containers on different platforms. While the X11-based display method can be conveniently deployed in the local environment by exposing a file socket from a container, deploying the image on a cloud and accessing it remotely is non-trivial.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work, GUIdock-X11 [3], is one of the solutions in bridging the graphical information from user and Docker containers by using the X11 common graphic interface. GUIdock-X11 passes the container X11 commands to a host X11 client, which renders the GUI.…”
Section: Introductionmentioning
confidence: 99%